MSMAD: a computationally efficient method for the analysis of noisy array CGH data - Budinská, Eva; Gelnarová, Eva; Schimek, Michael G (Bioinformatics, 2009)
MOTIVATION: Genome analysis has become one of the most important tools for understanding the complex process of cancerogenesis. With increasing resolution of CGH arrays, the demand for computationally efficient algorithms arises, which are effective in the detection of aberrations even in very noisy data.
Keywords: sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; algoritmy; financování organizované; Computational Biology; Programming Languages; Financing, Organized; programovací jazyk; srovnávací genomová hybridizace; Algorithms; Comparative Genomic Hybridization; Oligonucleotide Array Sequence Analysis; výpočetní biologie